Speaking Skills in Business Communication (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is about the need to teach language forms of business communication, the need to improve the linguistic competence of persons entering into social and legal relations, guiding people's actions, as linguistic competence becomes an indispensable component of general professional training of managers,municipal employees, assistants, managers of all levels in market conditions.